Safety, tolerability, and pharmacokinetics of VV116, an oral nucleoside analog against SARS-CoV-2, in Chinese healthy subjects - Qian, Hong-jie; Wang, Yu; Zhang, Meng-qi; Xie, Yuan-chao; Wu, Qing-qing; Liang, Li-yu; Cao, Ye; Duan, Hua-qing; Tian, Guang-hui; Ma, Juan; Zhang, Zhuo-bing; Li, Ning; et al. (Acta pharmacologica Sinica, 2022)
VV116 (JT001) is an oral drug candidate of nucleoside analog against SARS-CoV-2. The purpose of the three phase I studies was to evaluate the safety, tolerability, and pharmacokinetics of single and multiple ascending oral doses of VV116 in healthy subjects, as well as the effect of food on the pharmacokinetics and safety of VV116. Three studies were launched sequentially: Study 1 (single ascending-dose study, SAD), Study 2 (multiple ascending-dose study, MAD), and Study 3 (food-effect study, FE). A total of 86 healthy subjects were enrolled in the studies. VV116 tablets or placebo were administered per protocol requirements. Blood samples were collected at the scheduled time points for pharmacokinetic analysis. 116-N1, the metabolite of VV116, was detected in plasma and calculated for the PK parameters. In SAD, AUC and C max increased in an approximately dose-proportional manner in the dose range of 25–800 mg. T 1/2 was within 4.80–6.95 h. In MAD, the accumulation ratio for C max and AUC indicated a slight accumulation upon repeated dosing of VV116. In FE, the standard meal had no effect on C max and AUC of VV116. No serious adverse event occurred in the studies, and no subject withdrew from the studies due to adverse events. Thus, VV116 exhibited satisfactory safety and tolerability in healthy subjects, which supports the continued investigation of VV116 in patients with COVID-19.